2016
DOI: 10.1007/s00726-016-2332-y
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid levels of neuroactive amino acids in autism spectrum disorders: a review of the literature

Abstract: A review of studies on the body fluid levels of neuroactive amino acids, including glutamate, glutamine, taurine, gamma-aminobutyric acid (GABA), glycine, tryptophan, d-serine, and others, in autism spectrum disorders (ASD) is given. The results reported in the literature are generally inconclusive and contradictory, but there has been considerable variation among the previous studies in terms of factors such as age, gender, number of subjects, intelligence quotient, and psychoactive medication being taken. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 119 publications
(177 reference statements)
11
49
0
1
Order By: Relevance
“…Additionally, when stratified by severity of behavioral scores, we observe modest clustering according to plasma metabolites correlated to the disorder between the top and bottom quartiles of behavior severity groups for verbal, social, and ADOSS-SS metrics, but not for nonverbal, and less so with fecal samples (Figures 1N, S1H-S1I). These correlations support the involvement of lipid, amino acid, and xenobiotic metabolism in the etiology of ASD, as previously described (8,48,52), and reveal new candidates for ASD biomarkers that correlate with symptom severity.…”
Section: Global Metabolite Levels Correlate With Clinical Behavioral supporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, when stratified by severity of behavioral scores, we observe modest clustering according to plasma metabolites correlated to the disorder between the top and bottom quartiles of behavior severity groups for verbal, social, and ADOSS-SS metrics, but not for nonverbal, and less so with fecal samples (Figures 1N, S1H-S1I). These correlations support the involvement of lipid, amino acid, and xenobiotic metabolism in the etiology of ASD, as previously described (8,48,52), and reveal new candidates for ASD biomarkers that correlate with symptom severity.…”
Section: Global Metabolite Levels Correlate With Clinical Behavioral supporting
confidence: 87%
“…Amino acid signatures of oxidative stress and mitochondrial function are also present in our dataset. Dysregulated amino acid degradation, homeostasis, and import into the brain have been implicated as a cause of neuronal stress in ASD, and supporting metabolomic data has shown perturbations of various amino acid pathways, such as glutamate, methionine, glutathione, and gamma-glutamyl metabolites (10,17,24,26,29,33,49,52,76), which exhibit differences as well ( Figure 4E). We also demonstrate correlations between pathways of oxidative stress (cysteine, methionine, SAM and glutathione pathways) with the ADOS-SS ( Figure 4F).…”
Section: Asd Correlates With Cellular Energy and Oxidative Stress Metsupporting
confidence: 55%
“…Park et al reported that taurine, as an antioxidant and regulator of in ammation, might be a valid biomarker for ASD [46]. Combined with vitamin D3, taurine showed bene ts in the treatment of ASD [47][48]. All metabolic pathways interact with each other and constitute a complex network with related genes and diseases (Additional le 6: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids passing through the blood-cerebrospinal fluid barrier, such as phenylalanine, tyrosine, and tryptophan, are precursors of neurotransmitters regulating the functioning of the central nervous system that affect the emotional state and mood among others. In addition, the level of amino acids excreted with the urine provides important information about not only the dietary factors but also the factors connected with the digestive system affecting the occurrence and severity of autism symptoms [5,6]. Compounds containing a thiol group in their structure, such as homocysteine (Hcy), cysteine (Cys), glutathione (GSH), cysteinylglycine (CysGly), and γ-glutamylcysteine (γ-GluCys), play a significant role in living organisms.…”
Section: Introductionmentioning
confidence: 99%